Highly Recommended? How Relation-Specific Attachment Styles Bias Customers Willingness to Recommend - Verbeke, Willem J. M. I.; Gijsenberg, Maarten J.; Hendriks, Larissa M. E.; Bouma, Jelle T.; Teunter, Linda H. (Frontiers in Psychology, 2020)
Recently concepts from attachment theory are being applied to business situations. In this paper we focus on how relationship specific (RS) versus general (G) attachment styles affect the willingness-to-recommend (WtR) by customers. Such WtR refers to the likelihood of customers to recommend the services of their service provider to other customers, based on their experiences with the provider. This WtR is often measured by means of the Net Promoter Score (NPS) which is assumed to be a reliable (credible) market signal as it originates from customers themselves and not from the firm. This study provides insights in this issue using data from 798 members of an online panel from the Netherlands, covering four service industries. Customers are surveyed on their RS and G attachment styles, trust in, satisfaction with, and commitment to their service provider, as well as their WtR this provider. Findings emerge from econometric parallel mediation analyses. This study shows that customers’ RS but not the G attachment styles bias their appraisal of trust in, satisfaction with and commitment to the service provider, which in turn affects their WtR. More specifically, across the four service industries, customers scoring higher on RS anxiety and/or avoidance show systematically lower levels of trust in and satisfaction with, and commitment to the firm, ultimately leading to lower WtR. Firms should especially target those customers that score higher on RS avoidance (possibly in combination with higher levels of RS anxiety) as their WtR is strongly biased which might create uncertainty for other customers about the firm’s reputation.